Model Desain Pembelajaran Pendidikan Agama Islam di SMP Negeri 1 Kadipaten Kabupaten Tasikmalaya - Nasir, Tatang Muh; Hasbiyallah, Hasbiyallah; Dedih, Ujang; Fachriyah, Neng Vera (ARZUSIN, 2023)
This study aims to find an overview of the PAI learning design model in SMPN 1 Kadipaten Tasikmalaya Regency. This research uses a qualitative approach and the data sources are PAI teachers, class teachers and principals. This study used observation and interview techniques to collect data related to the research objectives. After the data is collected, the next stage is to analyze the data, in this case the researcher uses the approach of Miles et al, namely, data selection and data mapping, data presentation and perification and conclusions. This study found the following conclusions: the learning model applied by PAI teachers is the first active and cooperative learning model, which is a learning model that brings students to be active and creative, not only listening, but also carrying out activities such as processing, finding, and utilizing information. Second, the contextual learning model, this model helps educators relate the material taught to the real-world situation of students, thus allowing learners to find a connection between the knowledge they have and its application in their lives as family and community members.